Real-Time MRI Monitoring of GelMA-Based Hydrogel-Loaded Kartogenin for In Situ Cartilage Regeneration - Zhang, Hanyuan; Fang, Weijun; Zhao, Tingting; Zhang, Huabing; Gao, Liang; Li, Jingya; Wang, Rujing; Xu, Weiping (Frontiers in Bioengineering and Biotechnology, 2022)
The cartilage has poor ability to mount a sufficient healing response. Herein, kartogenin (KGN), an emerging stable nonprotein compound was grafted to resulting dopamine nanoparticles based on Fe (III) complexation, and followed by integrating into injectable hydrogels with tunable stiffness to obtain a desirable and simulating microenvironment that protected and promoted the growth of bone marrow mesenchyme stem cells (BMSCs). The in vitro results demonstrated that the KGN undergone long-term sustained release behavior and availably promoted the deep migration of BMSC cells in yielding hydrogels. And in vivo results showed that cartilage defect obtained significant regeneration post operation in 12th week, and the defect edge almost disappeared compared to adjacent normal cartilage tissue. Meanwhile, T2-weighted magnetic resonance imaging (MRI) property resulting from dissociative Fe (III) can significantly monitor the degradation degree of the implanted hydrogels in the defect site. This integrated diagnosis and treatment system gives insight cartilage regeneration.